Case report of twins with Bardet-Biedl syndrome exhibiting a rare mutation in the TTC8 gene - Agnieszka Murawska; Kamil Możdżeń; Grzegorz Horosin; Edward Pędziwiatr; Joanna Makowska; Jakub Pośpiech; Konrad Kaleta; Dorota Drożdż; Katarzyna Zachwieja (Pediatria Polska)
Bardet-Biedl syndrome (BBS) is a rare, autosomal recessive disorder, resulting from mutations in various genes, including TTC8. Abnormal variants in this gene were found in the case of our patients – twin sisters diagnosed with BBS. Next-generation sequencing revealed variants in the TTC8 gene: c.-104G>A [NM_001288783, rs119103286] and c.635T>C [NM_144596], which are associated with BBS type 8. The variant found in the patients’ mother was c.-104G>A, and in the patients’ father was c.635T>C, but they did not exhibit any BBS symptoms. Both twins presented several symptoms characteristic of BBS, such as retinopathy, visceral obesity, postaxial polydactyly, renal dysfunction, cognitive impairment, facial dysmorphia, and dental abnormalities. Table 1 compares BBS to other diseases, to facilitate differential diagnosis. Table 2 shows the symptoms of BBS and their frequency of occurrence and Table 3 compares cases of BBS with TTC8 mutation found in the literature.